Urea assisted pyrolysis of corn cob residue for the production of functional bio-oil. (April 2022) - Wu, Pei; Zhang, Xia; Li, Mengke; Yang, Jia; Peng, Xuanwei; Feng, Li; Jin, Ke; Wang, Jing; Zu, Bo
Abstract: Corn cob (CC) biomass nitrogen-enriched pyrolysis was carried out in a fixed bed with urea atmosphere at 300–600 °C, and formation mechanism of N-containing species was explored in depth. Results showed that urea assist pyrolysis greatly increased bio-oil and gas yields. H2 yield increased sharply to (19.3 vol%) and became the main composition at higher temperature, while CH4 and CO yield deceased, and the lower heating value of gas reached. For bio-oil, the content of phenols (main compositions) and N-containing species increased significantly, and the maximums reached 47.6% and 23.7%, respectively. While that of acetic acid, O-containing species (aldehydes/ketones/furans/esters) and aromatics decreased largely accordingly. For biochar, nitrogen content increased. The introduction of ammonia source can achieve the transformation of carbonyl compounds to nitrogen containing compounds. Possible reaction pathways of biomass N-enriched pyrolysis were proposed based on products evolution. In conclusion, biomass N-enriched pyrolysis could obtain high-valued N-containing chemical species and functional bio-char. Highlights: N-containing chemicals and bio-char are co-generated with ammonia source impregnated. Bio-oil yield (52.0 wt%) was enhanced with urea assist pyrolysis reaction. A large amount of N contained compounds was formed with urea assist pyrolysis. Bio-char was rich of nitrogen functionality.